Employee Wellbeing in Hybrid Work Environments: The Role of Work-Life Balance and Supervisor Support in Indonesia - R Rina Novianty Ariawaty; Imas Soemarayani; Kosasih Kosasih (International Journal of Applied Business and International Management, 2026)
This study examines how employee wellbeing is shaped in hybrid work environments by analyzing the roles of work–life balance and supervisor support within the Indonesian context. Although hybrid work is widely associated with increased flexibility, its implications for employee wellbeing remain uneven, particularly in socio-cultural settings characterized by hierarchical and relational workplace dynamics. Addressing this gap, the study integrates the Job Demands–Resources (JD-R) model and boundary theory to explain how organizational resources and boundary management processes jointly influence wellbeing outcomes. A quantitative approach was employed using survey data collected from 200 employees working under hybrid arrangements across urban and knowledge-intensive sectors in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among constructs. The results indicate that work–life balance has a strong positive effect on employee wellbeing (? = 0.46, p 0.001), highlighting boundary regulation as a central condition for sustaining wellbeing in hybrid work contexts. Supervisor support also exerts a significant direct effect on employee wellbeing (? = 0.31, p 0.001) and a strong effect on work–life balance (? = 0.53, p 0.001). Furthermore, work–life balance partially mediates the relationship between supervisor support and employee wellbeing (? = 0.24, p 0.001), indicating that supervisor support enhances wellbeing both directly and indirectly by enabling more effective boundary management. The model explains 47% of the variance in employee wellbeing, demonstrating moderate explanatory power. These findings show that employee wellbeing in hybrid work environments is not determined by flexibility alone, but by how work–life boundaries are structured and supported within organizational contexts. The study contributes to the literature by providing empirical evidence from a non-Western setting and by advancing an integrated theoretical perspective that positions work–life balance as a key mechanism linking job resources to wellbeing outcomes. Practically, the findings underscore the importance of supervisory practices in shaping boundary conditions and sustaining employee wellbeing under hybrid work arrangements.